2007
DOI: 10.1007/s00464-006-9181-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercostals neural blockade with Marcaine (bupivacaine) on postoperative pain after laparoscopic cholecystectomy

Abstract: Intercostals neural blockade may safely be used to reduce the postoperative pain after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It has been shown that continuous intercostal nerve blocks lead to better pain control in these patients. 158 For patients undergoing laparoscopic cholecystectomy, pain severity 159 and postoperative morphine consumption 160 were significantly reduced by intercostal nerve blockade. In addition, the duration of the need for patient-controlled analgesia was significantly decreased.…”
Section: Effectiveness One Of the Most Important Indications Formentioning
confidence: 99%
“…It has been shown that continuous intercostal nerve blocks lead to better pain control in these patients. 158 For patients undergoing laparoscopic cholecystectomy, pain severity 159 and postoperative morphine consumption 160 were significantly reduced by intercostal nerve blockade. In addition, the duration of the need for patient-controlled analgesia was significantly decreased.…”
Section: Effectiveness One Of the Most Important Indications Formentioning
confidence: 99%
“…Other anaesthetic techniques trialled have included epidural 77 and regional 78 anaesthesia. Only intercostal nerve blocks have been shown to reduce postoperative pain scores, although their clinical significance was debatable 78 (Level IB).…”
Section: Resultsmentioning
confidence: 99%
“…The methods most commonly used to reliably assess pain after LC are the 11-point Visual Analog Scale [17,18,27,38,[45][46][47][48][49][50][51][52], post-operative analgesic consumption [17,48,[53][54][55], or need for rescue analgesia [41,46,48,[56][57][58][59][60]. Post-operative pain is a highly individualized, subjective patient-reported appraisal; hence, patient-reported pain was selected as the means by which to record the primary study endpoint.…”
Section: Discussionmentioning
confidence: 99%